2019
DOI: 10.1371/journal.pone.0224017
|View full text |Cite
|
Sign up to set email alerts
|

Intubation with channeled versus non-channeled video laryngoscopes in simulated difficult airway by junior doctors in an out-of-hospital setting: A crossover manikin study

Abstract: Failure to secure the airway is an important cause of morbidity and mortality during resuscitations. We compared the rate of successful intubation of the King Vision™ aBlade™ channeled and non-channeled video laryngoscopes, and McGRATH™ MAC video laryngoscope when used by junior doctors to intubate a simulated difficult airway in an out-of-hospital setting. 105 junior doctors were recruited in a crossover study to perform tracheal intubation with the three video laryngoscopes on a simulated difficult airway us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Chew et al did a similar study on a cohort of military medical officers and found the intubation success rates were higher with channeled King Vision and McGrath as compared to the King Vision non-channeled laryngoscope [21]. This corroborated with our study findings.…”
Section: Discussionsupporting
confidence: 90%
“…Chew et al did a similar study on a cohort of military medical officers and found the intubation success rates were higher with channeled King Vision and McGrath as compared to the King Vision non-channeled laryngoscope [21]. This corroborated with our study findings.…”
Section: Discussionsupporting
confidence: 90%
“…Chew et al did a similar study on a cohort of military medical o cers and found the intubation success rates were higher with channeled King Vision and McGrath as compared to the King Vision non-channeled laryngoscope 21 . This corroborated with our study ndings.…”
Section: Discussionmentioning
confidence: 97%
“…Chew et al did a similar study on a cohort of military medical o cers and found the intubation success rates were higher with channeled King Vision and McGrath as compared to the King Vision nonchanneled laryngoscope 21 . This corroborated with our study ndings.…”
Section: Discussionmentioning
confidence: 97%